Influence of thermoplastic zein in PCL/TZ and HAp bio composite via solid state supercritical CO₂ foaming / Istikamah Subuki, Suffiyana Akhbar and Farrah Khalidah Nor Wahid - Subuki, Istikamah; Akhbar, Suffiyana; Nor Wahid, Farrah Khalidah (Universiti Teknologi MARA Shah Alam, 2020)
containing blended poly(ɛ-caprolactone) (PCL), hydroxyapatite (HA), and thermoplastic zein (TZ). Thermoplastic zein was developed by mixing zein with glycerol (GLY) and polyethylene glycol (PEG). The thermal properties of mixed TZ and bio composite were characterised to investigate the characterisation of PCL/TZ/HA composites. The bio composited was then molded, producing porous structure via solid state supercritical carbon dioxide (scCO2) foaming process. The specimen was saturated with CO2 for six hours at 50˚C and saturation pressure of 20MPa at a fast depressurisation rate. The morphology of the porous specimen produced was characterised using scanning electron microscopy (SEM). The results indicated that after polymer saturation with CO2, high depressurisation causes the formation of nucleated gas cells that give rise to pores within the foamed specimens. The blended bio composite with the composition of PCL60/TZ20/HAp20 exhibits a well interconnected porous structure compared to other bio composite prepared. The foaming effect produce foams with heterogeneous morphologies on bio composite material at relatively low temperature.